March 8th - Woman International Day - Rio de Janeiro Federal University - UNIRIO - celebrates women in a Scientific Lounge! - Isabel CF da Cruz (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2006)
Malvina Tuttman, UNIRIO´s chanceler, conduct a debate related to the women´s reproductive rights with her guests, Kleyde Ventura, Isabel Cruz, Laura Rónai, Ruth Serrão, Maria de Lourdes Naylor Rocha e Natália Fiche, in a beautiful lounge.